ANALISIS EFEKTIVITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Mandagi, Junisa; Sabijono, Harijanto; Walandouw, Stanley Kho (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The land and building title transfer duty is one of the regional tax that has large contribution as the receiver of the original local government revenue.One measure of the ability of regions to exploit the income is how much the local tax sector contributes to local revenues, especially local revenues that can later be used as a source of funds / expenses to meet the needs of local spending concerned. The purpose of this research is to know the affectiveness and the contribution of the land and building title transfer duty in manado city. The method that is used in this research is descriptive with using qualitative approach. Based on the result of this research, it shows that the effectiveness of the land and building title transfer duty in 2014-2017 is ratedÂ  quite effective, while in 2016 it was decreasing in the percentage, on the other hand, the contribuction of the land and building title transfer duty in original local government revenue was unstable from year to year. Keywords: Effectiveness, Contribution, Land and Building Title Transfer Duty, Original Local Government Revenue.